Preserving electronic records in Ghana: Implications for national heritage - Akussah, H. (Ghana Library Journal, 2002)
With the revolutionary global shift from print to electronic media as means of documentation and communication, the landscape of managing records is changing fast. In Africa, the public sector is more hit as n result of the lack of resources, legislative framework, infrastructure and institutional capacity. The article discusses the preservation of electronic documents in the public sector of Gitana and the implications for national heritage. It highlights key issues including, legislative reviews, technological support, staff re-engineering and capacity building and the active involvement of records and archives managers in the "conception" stage of electronic documents. enacting the Paperwork Elimination Act in 1995 (Ubogu 2001). On the contrary, Fitzgerald (1998) intimated that, the world will never see paper eliminated entirely but rather a society in which paper has a much diminished role. Whiles the debate is raging on in the developed countries, Africa being saddled with diminishing gross domestic products, ever soaring debt burdens, unfavourable trade balances and high inflationary trends is yet to start grappling with the pull and tug fashion with which rapidly changing technology is impacting on the institutions creating and managing records and archives.